Teachers’ Perceptions of English Teaching Strategies in the Current Curriculum Change - Amirullah Abduh; Geminastiti Sakkir; Rosmaladewi Rosmaladewi; Martin Andrew; Yasdin Yasdin (International Journal of Language Education, 2022)
This paper aims to explore teachers’ perceptions on the implementation of English teaching strategies in the current curriculum change.  The key question is that  what are the teachers' perceptions of English teaching strategies in the current curriculum change? This study was conducted in one of the Indonesian provinces with the participants of 102 English teachers. The instrument of data collection used Likert-scale questionnaires. The questionnaires contains specific questions on teachers’ responses on their strategies in relation to current curriculum reform. The data gained in this study was analysed using vocabulary statistics available in lextutor programs.  The result of the study shows that there is a majority of the English teachers in this study perceive that curriculum reforms have impacted positively on their teaching strategies and provide diverse categories of responses to change. The reason for this is that is a tendency of English teachers to upgrade their knowledge and skills to adapt with the change. In addition, teachers of English are recommended to learn about the essence of change so that they can implement the change successfully.